HERALDIC WOMEN IN THE SELJUK-BYZANTINE - Fatma İNCE (Fırat University, 2020)
In the Seljuks and even the first Turkish States before them, women have an important place in social and political life. In the Göktürk inscriptions, the woman's place and importance are mentioned, as well as in the Uighurs, since the chieftain of this tribe was busy with wars before the establishment of the state, his mother Uluğ Hatun looks at conflicts and lawsuits. Khagan and his wife were also required to ratify an interstate agreement. Otherwise, this agreement would be void.The Turks, after accepting Islam, maintained this important position within the women's state. When we look at the status of women belonging to the Seljuk dynasty, we see that they have military units, their own treasures and viziers in their orders. These women, who are strong enough to lead the destiny of the state, have even gone on the expedition when necessary. Although we do not have clear information about the lives of women in the Byzantine State, we can understand from the information we have that they do not have the same value given to women in Turkish society. However, the status of women belonging to the dynasty in the state is slightly different from that of women belonging to the public. Because they are the political transmitters of legitimacy and because of this they have an important position within the state. Dynastic women in the Byzantine State were to designate the new emperor either by becoming Regent of their sons or by marriage after the death of their wives. In this study, two contemporary States, The Great Seljuk State and the status of women in the Byzantine State, will be evaluated separately both socially and in terms of dynastic women.